Variability of Properties of Vibrio parahaemolyticus Strains Isolated from Individual Patients - Bhoopong, Phuangthip (American Society for Microbiology, 2007)
Infections by strains belonging to the O3:K6 pandemic clone of Vibrio parahaemolyticus are prevalent in southern Thailand, and serovariants of these strains have also been detected. V. parahaemolyticus strains lacking important virulence genes (tdh and trh) were isolated from 6.5 to 10.9% of clinical specimens during the period from 2000 to 2003. In order to understand whether changes to the characteristics of V. parahaemolyticus occur during infection, 10 isolates collected from each of 63 patients who presented with diarrhea at the Hat Yai hospital from 2003 to 2004 were examined for the presence of the tdh and trh genes, the O:K serotype, and genetic markers for the pandemic clone. A total of 42 patients (66.7%) yielded identical isolates (homogeneous populations), and 21 of the patients (33.3%) yielded isolates that differed in at least one character from the other isolates (heterogeneous populations). The DNA fingerprints (examined by arbitrarily primed PCR and pulsed-field gel electrophoresis) of some, but not all, of the heterogeneous populations from single patients were indistinguishable. The results indicated that some patients were infected with a unique strain and that in vivo changes (tdh deletion or serotype conversion) might have occurred in certain individuals. It is therefore important to bear in mind that epidemiological studies based on the analysis of a single colony from a single patient might lead to misleading conclusions. Finally, the present study did not rule out the possibility that isolates lacking tdh and trh have unknown virulence mechanisms other than the tdh and trh genes.